Actitudes morales y sociales en adolecentes - Knobel, Mauricio; de Perez Osorio, N. Delucca (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The Tsedek Test and the Rosenzweig Test were administered to 200 adolescents of La Plata, Argentina. Eighty subjects with complete data were selected. Seventy-one percent of them were considered average in reference to the capacity' to endure frustrating situations. Political, religious, and cultural attitudes could not be measured because the questionnaire given, although anonymous, aroused hostile reactions and opposition from the subjects.